A multidisciplinary approach for developing an assessment tool for touch screen devices. - Danial-Saad, Alexandra; Chiari, Lorenzo (Disability & Rehabilitation: Assistive Technology, 2018)
Aim: The aim of this study was to describe the processes of reaching consensus regarding the assessment of the user’s skills required to operate various touch screen devices. A five-step procedure was used to collect and validate the required skills by a multidisciplinary team of 52 experts. Content validity was calculated to determine the agreement levels between the experts. A comparison was made between the discipline groups in order to test correlation between each group and their choice of specific clusters of tasks. Methods: The final consensus set by the experts' recommendations included 15 domains and 50 skills/measurements. The result of Cronbach's α test for the final assessment questionnaire (50 skills/measurements) was 0.94, which indicates a high degree of internal consistency. The results of Kruskal-Wallis’s test showed the lack of any significant difference between agreements of the clinicians and the technicians groups, but significant differences were found between the educators and the clinicians groups. Conclusion: The assessment questionnaire, in its current form, can be used by clinicians and it is expected to help in developing an objective assessment tool to quantify the performance and touch characteristics of individuals with varying abilities and disabilities, in order to enhance accessibility of touch screen technology. Implications for Rehabilitation: Collecting and creating the required knowledge needed for assessing the user's skills for operating touch screen devices. The created knowledge helps clinicians to focus on the essential skills and measurements needed for a comprehensive assessment of the individual's abilities and disabilities while operating touch screen devices. The results of the assessment can be used as recommendations for enhancing accessibility of touch screen devices for various disabilities. This knowledge is expected to help in developing an application that provides an objective assessment tool. The study emphasizes the importance of close collaboration with multidisciplinary teams for creating a valid assessment tool.